(untitled) (Damascus University Journal of agriculture sciences, 2025)
This research was conducted to study both percentage and quality of olive oil extracted from some phenotypes of Khodeiri and Doebly varieties. It included the estimation of oil percentage in fruits. The physical and chemical characteristics of extracted oil (free fatty acids, peroxide index and specific absorbance 232 - 270nm were also studied. The results showed that the acidity of samples is not identical, ranging between 0.5 - 2.25. The highest acidity was for Khodeiri in Al-Mushayrafa. All oil samples were classified as extra virgin except for that of Khodeiri in Al-Mushayrafa which was classified as normal olive oil. The peroxide index was between 2 - 5.5 meq/kg. Dakrawi phenotype in Al-Sakhaba recorded the lowest peroxide value versus the highest value for Khodeiri in Al-Mushayrafa. The olive oil percentage of studied samples ranged between low for the phenotypes Dakrawi and Menqiri in Al-Dirana, medium for the phenotypes Doebly and Al-Darmlali, and high for Khodeiri. The percentage of myristic acid ranged between 9.72 - 9.78%, palmitic acid 12.90 - 13.04%, palmitoleic acid 14.32 - 14.41%, citric acid 16.46 - 17.43%, oleic acid 17.32 - 19.26%, linoleic acid 19.05 - 21.38%, linolenic acid 21.35 - 22.66%, and arachidic acid 24.09 - 24.24%.